Pengaruh Kapasitas Sumber Daya Manusia, Pengendalian Intern Akuntansi, Pemanfaatan Teknologi Informasi Dan Pengawasan Keuangan Daerah Terhadap Keterampilan Dalam Pelaporan Keuangan Pemerintah Daerah Kabupaten Sukoharjo (Studi Empiris Pada Badan Keuangan Daerah Kabupaten Sukoharjo Tahun 2017) - Pratama, Obrian Trisna; Anandita, Arnes (Universitas Merdeka Madiun, 2021)
Abstractâ€” This research aims to analyse and prove about the effect of human resource capacity, accounting internal control, use of information technology, and regional financial supervision on the reliability of local government financial reporting. This research object is the Regional Finance Agency of Sukoharjo Regency. The sampling method use purposive sampling. Number of respondent in this research were 50 employee. Data analysis method use multiple linier regression analysis. The research result show that human resource capacity, accounting internal control, use of information technology, and regional financial supervision effect on the reliability of local government financial reporting.Â Keywordsâ€”: Human Resource Capacity; Accounting Internal Control; Use of Information Technology; Regional Financial Supervision.